Discourse and knowledge a sociocognitive approach - Dijk, Teun A. van 1943- (New York Cambridge University Press, 2014)
"Most of our knowledge is acquired by discourse, and our ability to produce and understand discourse is impossible without the activation of massive amounts of knowledge of the world. Both 'discourse' and 'knowledge' are fundamental concepts of the humanities and social sciences, but they are often treated separately. Based on a theory of natural knowledge, the book deals with the cognitive processes, social distribution, cultural differences and the linguistic and discursive 'management' of knowledge in interaction and communication in epistemic communities. The first book to adopt a multidisciplinary approach to studying the relationship between the two concepts, Discourse and Knowledge introduces the new field of epistemic discourse analysis. Using a wide range of examples to illustrate the theory, it is essential reading for both students and academics interested in epistemology, linguistics, discourse analysis, cognitive and social psychology and the social sciences".
1. Introduction; 2. Elements of a theory of natural knowledge; 3. Discourse, knowledge and cognition; 4. Discourse, knowledge and social cognition; 5. Discourse, knowledge and society; 6. Discourse, knowledge and culture; 7. Language, discourse and knowledge; 8. Conclusions.
Prof. Phoebe Zoe Maria Sanchez (Recommending faculty) - Book 2019
Includes bibliographical references and index.
Keywords: Knowledge, Sociology of; Discourse analysis